Phthalocyanine compounds as corrosion inhibitors for metals in corrosive environment - Pesha, Thabo (My University, 2018)
The economy of nations depends highly on the industrial products which can be imported or exported. In addition, most industrial equipments such as engineering vehicles, reaction vessels and packaging machineries made from metallic products are prone to corrosion. One of the most efficient ways to mitigate corrosion process is through the use of chemical inhibition method. In this work, unsubstituted (CuPc, NiPc, ZnPc) and substituted phthalocyanines (TNCuPc, TNNiPc, TNZnPc) were synthesised and studied as corrosion inhibitors for aluminium (Al) metal in 1 mol. L-1 hydrochloric acid using gravimetric analysis, potentiodynamic polarisation (PDP) and electrochemical impedance spectroscopy (EIS) techniques. The synthesised inhibitors were characterised for their structure, spectroscopic and thermal properties using X-ray diffraction (XRD), ultraviolet visible (UV-vis), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). Both XRD and FTIR indicated a successful synthesis of all inhibitors investigated in the study. Nevertheless, the crystallinity of both ZnPc and TNZnPc was higher as compared to other inhibitors. TGA results showed that NiPc and TNNiPc are most thermally stable amongst the inhbitors studied. The gravimetric data revealed that the inhibition efficiencies decreased with an increase in temperature. Nonetheless, NiPc exhibited the highest inhibition efficiency of 96.42% at 40 ppm as compared to other inhibitors. The PDP results indicated that NiPc, ZnPc, TNNiPc and TNZnPc are mixed-type inhibitors with the exceptions of both CuPc and TNCuPc showing a physisorption adsorption mechanism. The adsorption of the studied inhibitors on Al metal obeyed the Lanmuir adsorption isotherm. The Gibbs free energy indicated that the adsorption process was spontaneous, and that the corrosion inhibition took place by physical adsorption process.
Thesis (M.Sc. (Chemistry)) --University of Limpopo, 2018
Keywords: Engineering; Metalic products; Chemical; Corrosion; Corrosion